1962
DOI: 10.1161/01.cir.26.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Malignant Tumors of the Pericardium

Abstract: Among 13,314 necropsies following death from neoplastic and nonneoplastic diseases performed at the Mayo Clinic from 1942 through 1958, 189 cases of secondary malignant lesions of the pericardium were demonstrated, an incidence of 1.42 per cent. Carcinoma of the lung and breast, the lymphomas, and leukemia constituted the large majority of the primary malignant lesions that caused the pericardial metastasis. Fifty-five of the 189 patients were adjudged to have had some impairment of cardiac function as a conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
1
4

Year Published

1979
1979
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(74 citation statements)
references
References 26 publications
0
69
1
4
Order By: Relevance
“…Patients are often asymptomatic, but they can also present with cardiorespiratory symptoms (for example, dyspnea, cough, chest pain), clinical signs (tachycardia, for instance), echocardiographic features of right heart compromise, and possibly life-threatening cardiac tamponade requiring emergency drainage 2 . Malignancies can involve the pericardium by four mechanisms: direct extension or metastatic spread via lymphatics or blood, chemotherapeutic toxicity, radiation toxicity, and opportunistic infections related to immunosuppressive therapies 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients are often asymptomatic, but they can also present with cardiorespiratory symptoms (for example, dyspnea, cough, chest pain), clinical signs (tachycardia, for instance), echocardiographic features of right heart compromise, and possibly life-threatening cardiac tamponade requiring emergency drainage 2 . Malignancies can involve the pericardium by four mechanisms: direct extension or metastatic spread via lymphatics or blood, chemotherapeutic toxicity, radiation toxicity, and opportunistic infections related to immunosuppressive therapies 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a review of 55 patients with cancer who had pericardial disease, Thurber and co-workers found that pericardial involvement resulted in or contributed significantly to the cause of death in 85% of patients. 11 Thus, therapeutic interventions directed at controlling this complication of malignancy can, if successful, result in prolonging survival. The overall survival and quality of life of patients with malignant pericardial effusion is dictated primarily by the histological type and extent of the underlying malignant process.…”
Section: Discussionmentioning
confidence: 99%
“…tributable to pericardial effusion [11]. In literature a highly variable incidence of cardiac metastases is reported, ranging from 2.3% and 18.3% [8,12].…”
Section: Case Reportmentioning
confidence: 99%